Investigation of Stress and Burnout Levels in Greek Nurses Working in Covid-19 Units / Clinics - Nikoletta Apostolidi; Theodora-Paisia Apostolidi; Konstantinos Tsaras and Maria Malliarou (Professor Despina Sapountzi-Krepia, 2024)
Investigation of Stress and Burnout Levels in Greek Nurses Working in Covid-19 Units / Clinics